PENGARUH PENGGUNAAN SMARTPHONE TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI SMAN 3 KEFAMENANU - Felisia Limun; Vinsensia Ulia Rita Sila; Muhammad Amran Shidik (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The purpose of this study was to determine the students' use of smartphones in Biology subjects in high school, to determine students' learning motivation in Biology subjects in high school, and to determine how much influence the use of smartphones had on learning motivation in Biology subjects in high school. This research was conducted at SMAN 3 Kefamenanu in the odd semester of T.A 2021/2022. This research is ex post facto research using a quantitative approach consisting of one independent variable and one dependent variable. The sample in this study were all students of MIA SMAN 3 Kefamenanu, totaling 42 students. Data collection techniques using questionnaires and documentation. There are 2 types of questionnaires, namely the smartphone use questionnaire and the learning motivation questionnaire. The data analysis technique used in this study was descriptive statistics and simple linear regression analysis. Based on the results of descriptive statistical tests, students' smartphone use is in the medium category, namely 72%, students' learning motivation is in the medium category, which is 67%, while the results of simple linear regression show that there is an effect of smartphone use on students' learning motivation, it can be seen that R Square is worth 0.003. It can be concluded that even though it is in a low category, the effect of smartphone use (X) on learning motivation (Y) is 3%.